EVALUATION OF AFRICAN TOMATO LANDRACES (SOLANUM LYCOPERSICUM) SUPPORTED MORPHOLOGICAL AND HUSBANDRY TRAITS - DR. NASOD RIZAE; KEMJI, P.E; DODE K.O., DR. NASOD RIZAE; KEMJI, P.E; DODE K.O. (International Journal of Multidisciplinary Research and Studies, 2021)
Crop a domesticated plant species which has developed largely adaptation to the natural and cultural environment in which it lives; therefore understanding and utilizing the genetic variation in tomato accessions area unit essential for raising the crop. The objective of this study was to characterize sixty-nine tomato landraces from the globe Vegetable Centre and therefore the National Gene bank of the African country to spot fascinating morphological and husbandry traits that could be used for tomato crop improvement. Field experiments were arranged to go into a randomized complete block style with 3 replicates at the University of Nairobi’s Kabete field station, Kenya, in 2014 and 2015. The principal component analysis showed that the first five components explained 78.4% of the total variation among the genotypes. Traits that contributed most to variability were the presence of inexperienced shoulder, fruit size, exterior fruit color, pubescence density, flower color, and fruit cross-section shape. Cluster analysis grouped the accessions into two major clusters. Cluster I contained sixty-three accessions whereas cluster II had six accessions. As the study was done on variance for quantitative traits indicated important variations among the accessions for single leaf area, soil-plant analysis development, days to five hundredth flowering, days to maturity, the number of fruits per plant, fruit width, fruit length, and fruit weight per plant. Fruit weight per plant ranged from 565.0 g to 2759.0 g per plant and showed a positive significant correlation with fruit length (r = 0.28) and fruit width (r = 0.30). The study showed the existence of wide genetic diversity among the tomato accessions so providing scope for future genetic improvement of the crop.